F FAKTOR FAKTOR YANG BERHUBUNGAN DENGAN PROGRAM RUJUK BALIK (PRB) PASIEN HIPERTENSI DI RSUD ALIMUDDIN UMAR KABUPATEN LAMPUNG BARAT - Sari, Lia Puspita; Rahayu, Dewi; Karyus, Aila; Pratiwi Putri, Dian Utama; Budiati, Endang (An Idea Health Journal, 2024)
Referral Program (PRB) is a health service program that is provided to JKN participants with chronic diseases with stable conditions and still requiring treatment at first-level health facilities. Hypertension is a chronic disease that can only be controlled and requires long-term and even lifelong treatment so that patient compliance with hypertension treatment is required. Patient compliance is a determining factor for the success of hypertension therapy with controlled blood pressure results. This study was to determine what factors are associated with visits to the Referback Program for Hypertensive Patients at Alimuddin Umar Hospital, West Lampung Regency. The population of this study were 135 patients in the Internal Medicine Polyclinic who were included in the research criteria. This research was conducted from August 2022. This research includes quantitative research with a Cross Sectional approach. Data collection using medical records. The results showed that there was a relationship between hospital facilities and DRR visits for hypertension patients, there was a relationship between the competence of health workers and DRR visits for hypertension patients, and there was a relationship between ease of information and PRB visits for hypertension patients. The ease of information variable is the dominant variable in the referral patient visit. It is necessary to monitor and evaluate the implementation of the Referback Program, to conduct more intensive socialization regarding the Referback Program, to Health Facilities or participants about how useful this referral programs.